A bargaining model of voluntary environmental agreements - Paola Manzini; Marco Mariotti (Fondazione Eni Enrico Mattei (FEEM), 2000)
We present an explicit model of firm-regulator negotiations in a market with several firms. We describe how the regulatory surplus is distributed between firms and regulator, and analyse the impact of various oligopoly parameters on the resulting level of environmental regulation. Our main result is that a "toughest firm principle" holds: the outcome of negotiations is essentially determined by the firm with the most aggressive attitude towards environmental control.
Keywords: 330; Umweltstandard; Selbstverpflichtung; Verhandlungstheorie; Oligopol; Theorie